Vaccination With Live Attenuated Vaccines in Four Children With Chronic Myeloid Leukemia While on Imatinib Treatment - Bettoni da Cunha-Riehm, Claudia; Hildebrand, Verena; Nathrath, Michaela; Metzler, Markus; Suttorp, Meinolf (Frontiers in Immunology, 2020)
Chronic myeloid leukemia (CML) in childhood and adolescence is a rare malignancy, which can successfully be treated with the tyrosine kinase inhibitor (TKI) imatinib. According to the current experience, treatment is necessary for years and is required in the majority of cases a lifelong time to control the malignant disease. To what extend imatinib causes immunosuppression in different age cohorts is discussed controversially. According to the package information leaflets and general medical recommendations live vaccines are contraindicated while individuals are exposed to imatinib treatment However, undervaccinated subpopulations in many countries worldwide nowadays allow the spread of vaccine-preventable viruses from infected persons maintaining a reservoir for recurrent infections. Particular, recent increases in reported cases of measles are observed which are part of a global rise that still continues. Due to the high contagiousness of the virus, near perfect vaccination coverage (herd immunity of 93 to 95%) is required to protect effectively against measles resurgence -a scenario which is not realistic any more in many countries. Delineating from the experience in pediatric trials with imatinib-based treatment of CML showing no increased rate of infections, we categorized the grade of immunosuppression by this TKI as only mild to moderate. When four teenagers with CML treated with imatinib were identified without protective measles and/or varicella titers, we carefully balanced the risks of a live vaccination against the advantages of being protected against vaccination-preventable diseases. After informed consent the four patients underwent live vaccination. Here we report that in all patients the safety of live vaccines could be documented. In addition, we give an overview on the criteria forming the basis for individual decisions on live vaccinations in CML patients treated with imatinib.